Perceptions of a psychoeducation program for caregivers of persons with dementia at end of life: a qualitative study. (1st February 2019) - Durepos, Pamela; Kaasalainen, Sharon; Carroll, Sandra; Papaioannou, Alexandra
ABSTRACT: Objectives: Caregivers (CG) of persons with dementia have described positive and challenging experiences related to caring for a person with a neurological disease. This study explored perceived benefits and challenges of a unique psychoeducation program provided at end of life (EOL) jointly attended by current and bereaved CGs of persons with dementia, residing in a hospital Specialized Care Unit. Method: Semi-structured interviews were held with sixteen participants and analyzed with content analysis. Results: Program benefits were perceived by CGs such as: (i) enhanced emotional well-being, (ii) increased feelings of preparedness for EOL, and (iii) personal growth into role models. Within the organization the program was perceived as promoting relationship-centered care and increasing resources. Challenges such as diverse CG preferences, day-time scheduling and limited involvement of unit staff were perceived as barriers. Conclusions: This program fills a gap in care for CGs at the critical stage of EOL with continuity into bereavement. Implications for practice include: increasing engagement of unit staff for involvement and tailoring of the program, and translation of the program into alternative settings like long-term care. Policies outlining the support needs and resources for CGs through EOL within and outside the hospital are necessary to ensure access and continuity of care.